Hospital Based Clinical Protocol for the Management of Gestational Trophoblastic Disease at Maternity and Women’s Hospital - Baral, Gehanath; Vaidya, Achala; Verma, Sheela (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5067 NJOG 2010 Jul-Aug; 5(1): 61-67